Fires in refugee and displaced persons settlements: The current situation and opportunities to improve fire prevention and control. Issue 5 (August 2016) - Kazerooni, Yasaman; Gyedu, Adam; Burnham, Gilbert; Nwomeh, Benedict; Charles, Anthony; Mishra, Brijesh; Kuah, Solomon S; Kushner, Adam L; Stewart, Barclay T
Highlights: Fires in humanitarian camps are a significant and increasingly common problem. Humanitarian agencies do not have fire safety guidelines commiserate with fire risk. Several innovations could prevent/control camp fires (e.g. safer stoves, fire retardant tarpaulins). Abstract: Introduction: We aimed to describe the burden of fires in displaced persons settlements and identify interventions/innovations that might address gaps in current humanitarian guidelines. Methods: We performed a systematic review of: (i) academic and non-academic literature databases; and (ii) guidelines from leading humanitarian agencies/initiatives regarding fire prevention/control. Results: Of the 1521 records retrieved, 131 reports described settlement fires in 31 hosting countries since 1990. These incidents resulted in 487 deaths, 790 burn injuries, displacement of 382, 486 individuals and destruction of 50, 509 shelters. There was a 25-fold increase in the rate of settlement fires from 1990 to 2015 (0.002–0.051 per 100, 000 refugees, respectively). Only 4 of the 15 leading humanitarian agencies provided recommendations about fire prevention/control strategies. Potentially useful interventions/innovations included safer stoves (e.g. solar cookers) and fire retardant shelter materials. Conclusion: The large and increasing number of fires in displaced persons settlements highlights the need to redress gaps in humanitarian fire prevention/control guidelines. The way forward includes: (i) developing consensus among aid agencies regarding fire prevention/control strategies; (ii) evaluating the impact of interventions/innovations on the burden of fires; and (iii) engaging agencies in a broader discussion about protecting camp residents from armed groups.